PENGAWASAN PENGELOLAAN DANA DESA OLEH INSPEKTORAT KABUPATEN BOGOR - Kurniasih, Esih Kurniasih; Azijah, Dewi Noor; Rizki, Mochamad Faizal (Program Studi Ilmu Pemerintahan FISIP Universitas Galuh, 2025)
Supervision of village fund management has become a discourse in government studies, the inspectorate has the responsibility to ensure that the management of village funds is carried out in a transparent and accountable manner. However, there is not much evidence of studies on the supervisory function of the inspectorate at the village level. This case study aims to explore the implementation of the supervisory function by the Bogor Regency Regional Inspectorate in the context of supervision of the village government. The main results were obtained from interviews, observations, and documentation. The data was analyzed using explanation building to identify the importance of the Inspectorate's involvement in the management of village funds with facts in the field. The results show that the supervisory function of the regional inspectorate of Bogor district still faces various challenges. The implications of this study are directed at improving the village fund supervision system and strengthening the capacity of the Inspectorate, with the aim of encouraging more responsible, transparent, and accountable fund management.